Old Las Vegas : Hispanic memories from the New Mexico meadowlands - García, Nasario (Lubbock, Tex. : Texas Tech University Press, 2005)
Oral history.
Text in English and Spanish.
Includes bibliographical references (page 296) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Hispanic Americans -- New Mexico -- Las Vegas Region -- Biography; Older people -- New Mexico -- Las Vegas Region -- Biography; Country life -- New Mexico -- Las Vegas Region -- Anecdotes; Country life -- New Mexico -- Anecdotes; Folklore -- New Mexico -- Las Vegas Region; Folklore -- New Mexico; Oral history; Las Vegas Region (N.M.) -- Social life and customs -- Anecdotes; New Mexico -- Social life and customs -- Anecdotes; Las Vegas Region (N.M.) -- Biography; Folklore -- Nouveau-Mexique.; Histoire orale; Nouveau-Mexique -- Mœurs et coutumes -- Anecdotes; oral histories (literary genre); SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Country life; Folklore; Hispanic Americans; Manners and customs; Older people; Oral history; New Mexico; New Mexico -- Las Vegas Region; Anecdotes; Biographies; Biographies; Biographies